Soil mesofaunal in constructed coal mining area - Oliveira Filho, Luís Carlos Iuñes (2015)
The objective was to evaluate the presence of meso-fauna soil in constructed soil after open pit coal mining in the Lauro Müller region, SC, Brazil. An experimental area of the Mina do Apertado and two reference areas (naturalized field and native forest) were used. The meso-fauna was collected using a 17 cm diameter metal cylinder, at 5 cm depth, and the extraction was performed by using the modified Berlese method, followed by the identification of organisms. The soil fauna was assessed by individual density and richness of groups and submitted to variance analysis and multivariate analysis of the data by correspondence analysis. A total of 19 taxa were found, and Acari, Collembola and Formicidae showed higher densities. The correspondence analysis showed a clear separation of anthropogenic sites (Mina do Apertado and naturalized field) from the reference area (native forest). Mina do Apertado recovery model groups showed similar reference to the native forest, satisfying the ecosystem services provided by them, promoting a suitable environment for groups of mesofaunal soil.